Enhanced Photovoltaic Performance of Polymer Hybrid Nanostructure Heterojunction Solar Cells Based on Poly(3-hexylthiophene)/ZnS/ZnO/Reduced Graphene Oxide Shell–Core Nanorod Arrays - Sookhakian, M.; Amin, Yusoff Mohd; Zakaria, Rozalina; Baradaran, S.; Mahmoudian, M.R.; Rezayi, M.; Tajabadi, M.T.; Basirun, Wan Jefrey (American Chemical Society, 2014)
A novel hybrid photoanode based on poly(3-hexylthiophene) (P3HT) modified ZnS/ZnO shell–core nanorod arrays was fabricated on indium tin oxide (ITO) modified reduced graphene oxide (rGO) film using a simple sequential electrodeposition process. The morphology and structure of the as-fabricated electrode were confirmed by X-ray diffraction, field emission electron microscopy, and high-resolution transmission electron microscopy. The electrochemical impedance spectroscopy and current–voltage curve measurements illustrated that the power conversion efficiency of the P3HT/ZnO nanorod arrays electrode was significantly improved by the formation of rGO film and type II band alignment in the heterostructure ZnS/ZnO shell–core nanorod arrays in the four-component P3HT/ZnS/ZnO/rGO electrode. On the basis of these results, P3HT as an excellent hole acceptor, ZnS as an electronic mediator, ZnO as an excellent electron acceptor and direct pathway, and rGO nanosheet as a superior conductive collector and transporter have been shown to have in total a significant effect on increasing photovoltaic efficiency.